Robust H Based PI Control Design for 2-DOF Helicopter: An LMI Approach - Goyal J.K.; Aggarwal S.; Ghosh S.; Kamal S. (My University, 2025)
This work presents a robust LMI tuned PI controller design for the real two degree of freedom (2-DOF) helicopter model with locating poles in a desired region. Experimental results are provided to demonstrate the effectiveness of the proposed design. © 2019 IEEE.